Learn from the Experts about Being Performance-First Jim Pierson - Pierson, Jim (O'Reilly Media, Inc., 2018)
In this interview, Ally MacDonald talks to Jim Pierson about how companies can make the shift to being "performance-first" at both a technical and organizational level. With over 20 years' experience in the Performance Engineering field, Jim Pierson has worked his way up the proverbial OSI stack. Jim got his start as a Green Beret radio communications chief in the Army. He then worked his way in the software industry from cable puller to network engineer and protocol analyst to tools developer. He is currently a principal architect at GoDaddy and has previously worked at Apple, Disney, SCEdison, and Microsoft